Impact of European Beech Forest Diversification on Soil Organic Carbon and Total Nitrogen Stocks–A Meta-Analysis - Rehschuh, Stephanie; Jonard, Mathieu; Wiesmeier, Martin; Rennenberg, Heinz; Dannenmann, Michael (Frontiers in Forests and Global Change, 2021)
Drought-sensitive European beech forests are increasingly challenged by climate change. Admixing other, preferably more deep-rooting, tree species has been proposed to increase the resilience of beech forests to drought. This diversification of beech forests might also affect soil organic carbon (SOC) and total nitrogen (TN) stocks that are relevant for a wide range of soil functions and ecosystem services, such as water and nutrient retention, filter functions and erosion control. Since information of these effects is scattered, our aim was to synthesize results from studies that compared SOC/TN stocks of beech monocultures with those of beech stands mixed with other tree species as well as monocultures of other tree species. We conducted a meta-analysis including 38 studies with 203, 220, and 160 observations for forest floor (i.e., the organic surface layer), mineral soil (0.5 m depth) and the total soil profile, respectively. Monoculture conifer stands had higher SOC stocks compared to monoculture beech in general, especially in the forest floor (up to 200% in larch forests). In contrast, other broadleaved tree species (oak, ash, lime, maple, hornbeam) showed lower SOC stocks in the forest floor compared to beech, with little impact on total SOC stocks. Comparing mixed beech-conifer stands (average mixing ratio with regard to number of trees 50:50) with beech monocultures revealed significantly higher total SOC stocks of around 9% and a smaller increase in TN stocks of around 4%. This equaled a SOC accrual of 0.1 Mg ha−1 yr−1. In contrast, mixed beech-broadleaved stands did not show significant differences in total SOC stocks. Conifer admixture effects on beech forest SOC were of additive nature. Admixing other tree species to beech monoculture stands was most effective to increase SOC stocks on low carbon soils with a sandy texture and nitrogen limitation (i.e., a high C/N ratio and low nitrogen deposition). We conclude that, with targeted admixture measures of coniferous species, an increase in SOC stocks in beech forests can be achieved as part of the necessary adaptation of beech forests to climate change.